Plant defense responses in opium poppy cell cultures revealed by liquid chromatography-tandem mass spectrometry proteomics - Zulak, Katherine; Khan, M.; Alcantara, J.; Schriemer, D.; Facchini, P. (AMER SOC BIOCHEMISTRY MOLECULAR BIOLOGY INC, 2009)
Opium poppy (Papaver somniferum) produces a diverse rarray of bioactive benzylisoquinoline alkaloids, including the narcotic analgesic morphine and the antimicrobial agent sanguinarine. In contrast to the plant, cell cultures of opium poppy do not accumulate alkaloids constitutively but produce sanguinarine in response to treatment with certain fungal-derived elicitors. The induction of sanguinarine biosynthesis provides a model platform to characterize the regulation of benzylisoquinoline alkaloid pathways and other defense responses. Proteome analysis of elicitor-treated opium poppy cell cultures by two-dimensional denaturing-polyacrylamide gel electrophoresis coupled with liquid chromatography-tandem mass spectrometry facilitated the identification of 219 of 340 protein spots based on peptide fragment fingerprint searches of a combination of databases. Of the 219 hits, 129 were identified through pre-existing plant proteome databases, 63 were identified by matching predicted translation products in opium poppy-expressed sequence tag databases, and the remainder shared evidence from both databases. Metabolic enzymes represented the largest category of proteins and included S-adenosylmethionine synthetase, several glycolytic, and a nearly complete set of tricarboxylic acid cycle enzymes, one alkaloid, and several other secondary metabolic enzymes. The abundance of chaperones, heat shock proteins, protein degradation factors, and pathogenesis-related proteins provided a comprehensive proteomics view on the coordination of plant defense responses. Oualitative comparison of protein abundance in control and elicitor-treated cell cultures allowed the separation of induced and constitutive or suppressed proteins. DNA microarrays were used to corroborate increases in protein abundance with a corresponding induction in cognate transcript levels. © 2009 by The American Society for Biochemistry and Molecular Biology, Inc.